Reversibility of alexithymia with effective treatment of moderate‐to‐severe psoriasis: longitudinal data from EPIDEPSO. (26th November 2018) - Sampogna, F.; Puig, L.; Spuls, P.; Girolomoni, G.; Radtke, M.A.; Kirby, B.; Brunori, M.; Bergmans, P.; Smirnov, P.; Rundle, J.; Castiglia, A.; Lavie, F.; et al.
Summary: Background: Alexithymia refers to difficulty in identifying and expressing emotions. Alexithymia is associated with high burden of disease in patients with psoriasis. Objectives: To investigate whether alexithymia was reversible in patients with psoriasis following real‐life therapeutic intervention. Methods: The Epidemiological Study in Patients with Recently Diagnosed Psoriasis (EPIDEPSO; NCT01964443) was a 1‐year multicentre observational study investigating the prevalence of alexithymia and other psychosocial comorbidities in patients with psoriasis with ≤ 10 years' disease duration and eligible for systemic treatment. Alexithymia was assessed using the Toronto Alexithymia Scale (TAS‐20) at baseline, 6 months and 1 year. Results: There was a statistically significant decrease in the prevalence of alexithymia in the follow‐up cohort, from 26·7% at baseline to 21·2% at 6 months and 18·8% at 1 year. More than half of the patients ( n  =   77, 53·8%) who were alexithymic at baseline experienced reversion of their alexithymia. Reversion of alexithymia was higher in patients who reached a high level of disease control, defined as ≥ 75% or ≥ 90% improvement in Psoriasis Area and Severity Index. Reversion of alexithymia was associated with dramatic improvement in quality of life, anxiety and depression. Moreover, hazardous alcohol use, highly prevalent in patients with alexithymia, was reduced almost threefold at 1 year. Conclusions: Alexithymia and associated high disease burden may be reversible in patients with effective treatment of psoriasis. Proactive recognition of patients who are unable to identify and express their feelings is important. Abstract : What's already known about this topic? Alexithymia, the inability to identify and express emotions, is highly prevalent in patients with psoriasis. Patients with alexithymia have a high disease burden, with impaired quality of life, anxiety and depression. What does this study add? Alexithymia may be reversible in patients with psoriasis. Higher psoriasis clearance is associated with a lower prevalence of alexithymia at 1 year. Anxiety, depression and harmful alcohol use are reduced in patients who have a reversion in alexithymia. Linked Comment:  Misery. Br J Dermatol 2019;180 :261 . Plain language summary available online Respond to this article